Sound Mimicry: An Old Trait of the New Music? - Almazova, Nina (Hyperboreus, 2019)
The use of musical means to imitate non-musical sounds is often identiﬁed as a characteristic of the New Music (an avant-garde trend reported to have developed in Ancient Greece beginning around 450 BC), although it can be traceable to an earlier period (at least to 584 BC). This paper reviews existing evidence on sound mimicry in the Classical period and considers its possible connections with the New Music. Particular attention is paid to distinguishing between vocal and instrumental sound imitation, and separating onomatopoeic effects from other types of mimesis somehow connected with music in texts. (I) The limited evidence that focuses directly on famous artists of the New Music (Timotheus and Philoxenus) leaves no doubt that they used sound mimicry, probably both by means of voice and instruments. However, there is no clear indication that the use of such effects was criticized for its innovation. (II) According to Plato, in his time sound mimicry through the human voice was unexpectedly widespread in poetry; he also speaks of it as a recognized feature of purely instrumental virtuoso music. Plato disapproved of such senseless trickery, but his condemnations are not related to his complaints about the recent degradation in music, and on the whole the New Music cannot be blamed for everything Plato disliked in this art (such as wind instruments or melodies without words). Still, in view of the fact that earlier lyrics, as far as we know, showed little evidence of sound mimicry, it may be cautiously conjectured that it was propagated in “high-style” sung poetry during the second half of the ﬁfth century BC. (III) Vocal onomatopoeic effects were mastered by Old Comedy, it may be postulated, even prior to Aristophanes. Even if some passages that contain sound imitation may be interpreted as Aristophanes’ pastiches or parodies of the New Music, it is impossible to prove that this device was an object, rather than a means, of mockery. If indeed it began to spread in monodic and choral lyrics in the second half of the ﬁfth century, we need not think that it was borrowed from comedy rather than instrumental music. Perhaps some critics felt that sound mimicry, with its comic potential, especially on human lips, was as much out of place in serious poetic genres as it was at home in comedy, but we have no evidence that speciﬁcally claims this. Onomatopoeia was not in itself a novelty, but its use may illustrate features of the New Music such as the confusion of genres, the increasing importance of instrumental parts and the growing numbers of sounds and scales.